Effects of diethylpropion treatment and withdrawal on aorta reactivity, endothelial factors and rat behavior - Da Silva, LBB; Cordellini, S. (Elsevier B.V., 2003)
Diethylpropion (DEP) is an amphetamine-like compound used as a coadjutant in the treatment of obesity and which presents toxicological importance as a drug of abuse. This drug causes important behavioral and cardiovascular complications; however, the vascular and behavioral alterations during DEP treatment and withdrawal, have not been determined. We evaluated the effects of DEP treatment and withdrawal on the rat aorta reactivity to noradrenaline, focusing on the endothelium, and the rat behavior during DEP treatment and withdrawal. DEP treatment caused a hyporreactivity to noradrenaline in aorta, reversible after 2 days of withdrawal and abolished by both the endothelium removal and the presence of L-NAME, but not by the presence of indomethacin. Furthermore, DEP treatment increased the general activity of rats. Contrarily, DEP withdrawal caused a decrease in the locomotor activity and an increase in grooming behavior, on the 2nd and 7th days after the interruption of the treatment, respectively. DEP treatment also caused an adaptive vascular response to noradrenaline that seems to be dependent on the increase in the endothelial nitric oxide system activity, but independent of prostaglandins synthesis. The data evidenced chronological differences in the adaptive responses of the vascular and central nervous systems induced by DEP treatment. Finally, a reversion of the adaptive response to DEP was observed in the vascular system during withdrawal, whereas a neuroadaptive process was still present in the central nervous system post-DEP. These findings advance on the understanding of the vascular and behavioral pathophysiological processes involved in the therapeutic and abusive uses of DEP. (C) 2003 Elsevier B.V. (USA). All rights reserved.
Keywords: diethylpropion; endothelium; nitric oxide; reactivity of rat aorta; behavior; treatment; withdrawal